The Role of Nrf2/sMAF Signalling in Retina Ageing and Retinal Diseases - Jialing Zhang; Ting Zhang; Shaoxue Zeng; Xinyuan Zhang; Fanfan Zhou; Mark C. Gillies; Ling Zhu (Biomedicines, 2023)
Age-related diseases, such as Parkinson’s disease, Alzheimer’s disease, cardiovascular diseases, cancers, and age-related macular disease, have become increasingly prominent as the population ages. Oxygen is essential for living organisms, but it may also cause disease when it is transformed into reactive oxygen species via biological processes in cells. Most of the production of ROS occurs in mitochondrial complexes I and III. The accumulation of ROS in cells causes oxidative stress, which plays a crucial role in human ageing and many diseases. Nuclear factor-erythroid 2-related factor 2 (Nrf2) is a key antioxidant transcription factor that plays a central role in many diseases and ageing in general. It regulates many downstream antioxidative enzymes when cells are exposed to oxidative stress. A basic-region leucine zipper (bZIP) transcription factor, MAF, specifically the small MAF subfamily (sMAFs), forms heterodimers with Nrf2, which bind with Maf-recognition elements (MAREs) in response to oxidative stress. The role of this complex in the human retina remains unclear. This review summarises the current knowledge about Nrf2 and its downstream signalling, especially its cofactor—MAF, in ageing and diseases, with a focus on the retina. Since Nrf2 is the master regulator of redox homeostasis in cells, we hypothesise that targeting Nrf2 is a promising therapeutic approach for many age-related diseases.